2005
DOI: 10.1007/s00125-005-1850-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum adiponectin levels in type 1 diabetic patients with microvascular complications

Abstract: Aims/hypothesis: Low serum adiponectin (ADPN) has been associated with increased risk of cardiovascular disease (CVD) and retinopathy in patients with type 2 diabetes mellitus. In type 1 diabetic patients, the relationship between ADPN and the presence of vascular complications is largely unknown. Methods: We investigated the relationship between serum ADPN and the presence of retinopathy, nephropathy and CVD in patients with type 1 diabetes, divided into matched groups with normoalbuminuria and no retinopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
177
4
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 213 publications
(213 citation statements)
references
References 51 publications
28
177
4
4
Order By: Relevance
“…Previous cross-sectional studies in adults with type 1 diabetes have shown a variable relationship between adiponectin levels and glycaemic control, with a negative [1], a positive [11] or no correlation at all [13]. In these studies, differences between the sexes were either not found or not reported.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Previous cross-sectional studies in adults with type 1 diabetes have shown a variable relationship between adiponectin levels and glycaemic control, with a negative [1], a positive [11] or no correlation at all [13]. In these studies, differences between the sexes were either not found or not reported.…”
Section: Discussionmentioning
confidence: 56%
“…Adiponectin Serum adiponectin was analysed with an inhouse time-resolved immunofluorometric assay based on commercial reagents (R & D Systems, Abingdon, UK) as recently described [13]. All samples were analysed in duplicates in a final dilution of 1:206.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The glucagon assay (developed in J. Holst's laboratory in Copenhagen, Denmark) is highly specific for the free C terminus of the molecule, and therefore specific for pancreatic glucagon, with the following assay characteristics: sensitivity <1 pmol/l, within-assay CV <5% at 20 pmol/l, between-assay CV <12%. Serum adiponectin was assayed by a novel, in-house timeresolved immunofluorimetric method, previously described in detail [15], which measures total circulating adiponectin (including high-and low-molecular-mass isoforms).…”
Section: Study Participantsmentioning
confidence: 99%
“…IFG and IGT were grouped together as IGR (n=152 or 11.7% of the total cohort). Insulin sensitivity was expressed as the ratio of the M value, averaged over the final 40 min of the 2 h clamp and normalised for fat-free mass (FFM; measured by electrical bioimpedance [15] In either sex, glucagon and proinsulin increased across sex-specific quartiles of IR, whereas adiponectin displayed the opposite trend (p≤0.02 for all; Fig. 1).…”
Section: Study Participantsmentioning
confidence: 99%